2016
DOI: 10.1371/journal.pone.0162156
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Incident Syphilis in a Cohort of High-Risk Men in Peru

Abstract: BackgroundSyphilis is concentrated among high-risk groups, but the epidemiology of syphilis reinfection is poorly understood. We characterized factors associated with syphilis incidence, including reinfection, in a high-risk cohort in Peru.MethodsParticipants in the NIMH CPOL trial were assessed at baseline and 2 annual visits with HIV/STI testing and behavioral surveys. Participants diagnosed with syphilis also attended 4- and 9-month visits. All participants underwent syphilis testing with RPR screening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
1
7
0
6
Order By: Relevance
“…The disease can be transmitted by a pregnant woman to her unborn baby in utero [2], leading to neonatal death, blindness in the newborn and severe disability in infants [3]. Major risk factors that promote the transmission of syphilis include men having sex with men, having concurrent multiple sex partners, alcohol or drug use and engaging in unprotected sex [4].…”
Section: Introductionmentioning
confidence: 99%
“…The disease can be transmitted by a pregnant woman to her unborn baby in utero [2], leading to neonatal death, blindness in the newborn and severe disability in infants [3]. Major risk factors that promote the transmission of syphilis include men having sex with men, having concurrent multiple sex partners, alcohol or drug use and engaging in unprotected sex [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fatores associados à transmissão vertical e maior incidência estão relacionados, também, a menor escolaridade materna, cor da pele, menor proporção de consultas e realização de exames no período gravídico (DOMINGUES & LEAL, 2016;VALLEJO & CIFUENTES, 2015). A prevalência e o perfil epidemiológico da sífilis apareceram com mais frequência, assim como a sua forma de transmissão, os métodos de diagnósticos mais eficazes e o tratamento (PINTO, 2016;LIU, 2016;TAYLOR, 2016;MALLMA, 2016;MUTAGOMA, 2016;PARK, 2016;ALMEIDA, 2015;CUNHA, 2015;DOMINGUES, 2014;SERAFIM, 2014;SMIT, 2013;LI, 2013;JAFARI, 2013;MIRANDA, 2012;CAVALCANTE, 2012;GALATOIRE, 2012;HOLANDA, 2011;DIÉZ, 2011;GONÇALVES, 2011;CARVALHO, 2009;ISAM, 2009;SANTOS, 2009;TAYRA, 2007;CONDE-CONZÁLEZ, 2007).…”
Section: Resultsunclassified
“…Em relação a prevalência da sífilis, Mutagoma et al (2016) e Miranda et al (2012) identificaram que a maior prevalência da doença foi em pessoas de baixa escolaridade, classe média baixa, com maior índice em mulheres do que em homens, residentes em área urbana e pacientes HIV positivos. Park et al (2016) retratam em um caso coorte, que houve uma reincidência de 56% da sífilis comparando-se um grupo de homens sem tratamento e 28% em homens já tratados, enquanto a prevalência em homens infectados com o vírus HIV foi de 2,8%.…”
Section: Prevalência Da Sífilisunclassified
“…While HIV prevention programs have followed local epidemiology in targeting MSM, the prevalence of HIV among Peruvian MSM remained stable between 2002 (13.9%) and 2016 (15.2%) [1, 2]. Moreover, in studies as recent as 2016, 69–70% of MSM in Peru reported condomless anal intercourse (CAI) with one or more partners in the last 3 months [3, 4]. While a few studies worldwide have explored how the location where a sexual contact occurs influences sexual risk-taking behavior among MSM, the potential influence of different social environments on condom use by MSM in Peru has not yet been studied [5].…”
Section: Introductionmentioning
confidence: 99%